GENETIC PROGRESS IN EARLY HYBRID (F 1 F4) POPULATIONS ARISING FROM CROSSES AMONG FOUR SOLANUM (E GG PLANT) GENOTYPE - A. I.Atugwu; V. N.Onyia; B. I.Soluobi; E.I. Eze; C. Chukwu (Journal of Animal and Plant Sciences, 2019)
Assessment of genetic progress is a very important tool in plant breeding programs. The objective of this study was to ascertain the genetic progress made in early hybrid (1-4) generations to identify the outstanding hybrid(s) that would be advanced to higher generations. The research was carried out at the teaching and research farm of the Department of Crop Science University of Nigeria, Nsukka during 2014 to 2016. Parents and hybrid generations from F1 to F4 were evaluated for the major yield contributing traits (number of flowers and fruits per plant, Plant height (cm), fresh fruit weight (g) and average fruit weight (g) ). The materials used include the parents: Yalo (solanum melongena), Jos (solanum gilo), Nsukka Local (Solanum macrocapon) and Nsukka indigenous (solanum aethiopicum) and their F1  to F4 progenies obtained from crossing and subsequent selfing. Genetic progress made at difference generations were obtained using Relative Performance Differential Analogue to Single Parent Heterosis analytical tool. Among the cross combinations, Yalo × Jos with genetic gain of 442.10%  and Nsukka Local × Yalo(139.27%)  were endowed for prolific flowering and fruiting. Yalo × Jos exhibited the highest genetic for fresh fruit weight (838.71%). Exploitation of these traits in the subsequent generations will improve the yield of solanum.
Keywords: Solanum; Genetic progress; Hybrids and Heterosis